Influence Of Elevated Temperature On The Fatigue Fracture Surface Hardness Of AA6061 - Zakaria, Kamarul Ariffin; Abdullah, Shahrum; Ghazali, Mariyam Jameelah; Ali, Mohd Basri (Medwell Journals, 2016)
-